Effects of oral hygiene using chlorhexidine on preventing ventilator-associated pneumonia in critical-care settings: A meta-analysis of randomized controlled trials - Hiroshi Hoshijima; Norifumi Kuratani; Risa Takeuchi; Toshiya Shiga; Eiji Masaki; Katsushi Doi; Nobuyuki Matsumoto (Elsevier, 2013)
Background/purpose: Ventilator-associated pneumonia (VAP) is one of the most frequent causes of morbidity and mortality among mechanically ventilated patients in critical care. Previous meta-analyses demonstrated that oral chlorhexidine (CHX) is beneficial in preventing VAP. Several new studies on oral hygiene as a preventive measure for VAP have been published. Considering all the currently available evidence together, an updated meta-analysis was conducted to evaluate the efficacy of oral CHX in preventing VAP. Materials and methods: A comprehensive literature search was conducted to identify clinical trials comparing oral hygiene care using CHX with conventional care in terms of the incidence of VAP. Two reviewers independently assessed each report to confirm that all reports met the inclusion criteria. The data from each trial were combined using the Mantel-Haenszel fixed-effects model to calculate the pooled relative risk and the corresponding 95% confidence intervals. Funnel plots were used to assess publication bias. Results: Nine randomized controlled trials met our inclusion criteria. Overall, 1623 patients received oral hygiene with CHX and 1662 received a placebo. The heterogeneity of the data was statistically refuted. Oral hygiene using CHX resulted in a reduced incidence of VAP (relative risk=0.59; 95% confidence interval, 0.47-0.73; P<0.001; I2=27.8%) according to a fixed-effects model. Publication bias was not apparent in the funnel plots. Conclusion: The analysis showed that oral CHX decontamination significantly reduced the incidence of VAP but not the mortality rate.